2020
DOI: 10.1200/jco.2020.38.15_suppl.6031
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy after concurrent chemoradiation therapy for locally advanced cervical cancer.

Abstract: 6031 Background: Standard treatment nowadays for locally advanced cervical cancer (LACC) is concurrent chemoradiation therapy (CCRT). However, due to distant metastasis, survival outcomes are still not optimistic. We tried to evaluate the clinical efficacy and safety of adjuvant chemotherapy for patients with LACC after treated with concurrent chemoradiation therapy (CCRT). Methods: Patients diagnosed between May, 2013 to May, 2018 with stage IIA-IIIB LACC were retrospectively analyzed. All the patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, it has been reported that recurrence or metastasis occurs in 35-40% of LACC patients after chemoradiotherapy, with a 5-year OS of only 70% (5,16). The current study concluded that consolidation chemotherapy after CCRT not only improved PFS and OS in LACC patients (17) but also increased the incidence of grade 3 and 4 bone marrow suppression (P<0.05) (18). RTOG 0417 was a clinical trial of bevacizumab (an anti-angiogenic agent) combined with CCRT as the primary treatment for LACC patients.…”
Section: Discussionmentioning
confidence: 76%
“…However, it has been reported that recurrence or metastasis occurs in 35-40% of LACC patients after chemoradiotherapy, with a 5-year OS of only 70% (5,16). The current study concluded that consolidation chemotherapy after CCRT not only improved PFS and OS in LACC patients (17) but also increased the incidence of grade 3 and 4 bone marrow suppression (P<0.05) (18). RTOG 0417 was a clinical trial of bevacizumab (an anti-angiogenic agent) combined with CCRT as the primary treatment for LACC patients.…”
Section: Discussionmentioning
confidence: 76%
“…Though not standard practice, adjuvant chemotherapy in cervical cancer has been examined in various settings, especially in advanced non-metastatic disease 18 23 24 25 26 . Earlier studies with mitomycin and 5-FU as adjuvant treatment did not prove to beneficial 23 , whereas studies with cisplatin plus gemcitabine were associated with increased toxicity, though beneficial 18 .…”
Section: Consolidation Systemic Therapy After Concurrent Chemotherapy...mentioning
confidence: 99%
“…On a similar note, the ACTLACC trial 25 tested paclitaxel plus carboplatin as adjuvant therapy after CCRT but was closed prematurely as there was no significant improvement in response rate and survival 25 . A large RCT was recently presented at ASCO (Americian Society of Clinical Oncology) comparing CCRT followed by adjuvant chemotherapy versus CCRT alone for locally advanced (stage IIA-IIIB) cervical cancers 26 , reporting failure to achieve benefits for adjuvant chemotherapy with increasing toxicity 26 .…”
Section: Consolidation Systemic Therapy After Concurrent Chemotherapy...mentioning
confidence: 99%